2017
DOI: 10.1093/ajcp/aqw225
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of the Bruker MALDI Biotyper CA System for the Identification of Clinically Important Bacteria and Yeasts

Abstract: The Bruker MALDI Biotyper CA System accurately identifies most clinically important bacteria and yeasts and has optional processing methods to improve isolate characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…However, the non-genomic nature of this method limits the phylogenetic investigation of closely related species or strains. This method is also limited by the comprehensiveness of the database used to compare spectra, which to date are heavily biased towards medically relevant pathogens [42]. Classification using 16S rRNA sequences and ANI provided limited taxonomic resolution and thus, less confidence in species identification [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, the non-genomic nature of this method limits the phylogenetic investigation of closely related species or strains. This method is also limited by the comprehensiveness of the database used to compare spectra, which to date are heavily biased towards medically relevant pathogens [42]. Classification using 16S rRNA sequences and ANI provided limited taxonomic resolution and thus, less confidence in species identification [43].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the broader utility of the NIH Mold Database beyond our institution, a multicenter study including eight US academic institutions was conducted. Unlike multicenter bacterial and yeast studies for which excellent inter- and intra-laboratory reproducibility has been demonstrated (Westblade et al, 2015; Wilson et al, 2017), this study has highlighted significant performance variability between instruments regardless of acquisition parameters and demonstrated that development of a specific mold standard is required for successful use of MALDI-TOF MS for mold identification.…”
Section: Introductionmentioning
confidence: 91%
“…Marucco et al compared identification of Candida species obtained by BD Phoenix (Becton Dickinson, Franklin Lakes, NJ, USA) and the Bruker system using 192 isolates from the strain collection of the Mycology Network of the Autonomous City of Buenos Aires, Argentina, reporting an observed concordance of 95%, with 5% of isolates not correctly identified by the BD Phoenix system [35]. Wilson et al reported results of a multicenter assessment of the Bruker MALDI Biotyper CA system for identification of clinically significant bacteria and yeasts, including 815 yeast isolates evaluated using three processing methods [36]. The percentage identified and the percentage identified with a high level of confidence were 98% and 88%, respectively, with the extended direct transfer method being superior to the direct transfer method (74% and 49% success, respectively) [36].…”
Section: Yeasts With a Focus On Candida And Cryptococcus Speciesmentioning
confidence: 99%
“…Wilson et al reported results of a multicenter assessment of the Bruker MALDI Biotyper CA system for identification of clinically significant bacteria and yeasts, including 815 yeast isolates evaluated using three processing methods [36]. The percentage identified and the percentage identified with a high level of confidence were 98% and 88%, respectively, with the extended direct transfer method being superior to the direct transfer method (74% and 49% success, respectively) [36]. Turhan et al assessed the Bruker system with 117 yeasts, including 115 candidemia-associated Candida species, reporting 98% and 87% identification to the genus- and species-level, respectively [37].…”
Section: Yeasts With a Focus On Candida And Cryptococcus Speciesmentioning
confidence: 99%